2021
DOI: 10.3390/su13041706
|View full text |Cite
|
Sign up to set email alerts
|

Adventure Tourism in the Spanish Population: Sociodemographic Analysis to Improve Sustainability

Abstract: In recent decades, tourism is an activity in continuous growth and generates a significant impact in the social, economic, and environmental fields. Adventure tourism mainly takes place in natural settings, where tourist immersion will generate, in addition to profits, an impact on nature and the conservation of natural areas. The purpose of this work is to analyze the sociodemographic characteristics of tourists who choose to carry out adventure activities, as well as the means of transport used. For this, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Similarly, Kaynak et al (1996) find that, in Dublin (Ireland), married people are more attracted by restful and physically refreshing destination attributes, while single tourists tend to value more the experiences associated with excitement, nature, fun, amongst other attributes. For the Spanish case, Rojo-Ramos et al (2021) find that amongst the marital status category, single tourists are more oriented toward adventure tourism activities. Based on Nicolau (2010), the spirit of variety-seeking for man-made attractions (in tourists from relatively smaller cities) is likely more pronounced in single and divorced tourists than married tourists.…”
Section: Tourists' City Of Origin: a Source Of Heterogeneitymentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, Kaynak et al (1996) find that, in Dublin (Ireland), married people are more attracted by restful and physically refreshing destination attributes, while single tourists tend to value more the experiences associated with excitement, nature, fun, amongst other attributes. For the Spanish case, Rojo-Ramos et al (2021) find that amongst the marital status category, single tourists are more oriented toward adventure tourism activities. Based on Nicolau (2010), the spirit of variety-seeking for man-made attractions (in tourists from relatively smaller cities) is likely more pronounced in single and divorced tourists than married tourists.…”
Section: Tourists' City Of Origin: a Source Of Heterogeneitymentioning
confidence: 86%
“…(1996) find that, in Dublin (Ireland), married people are more attracted by restful and physically refreshing destination attributes, while single tourists tend to value more the experiences associated with excitement, nature, fun, amongst other attributes. For the Spanish case, Rojo-Ramos et al. (2021) find that amongst the marital status category, single tourists are more oriented toward adventure tourism activities.…”
Section: Literature Reviewmentioning
confidence: 86%
“…As for gender, previous research had already pointed out possible distribution differences in terms of professional status, marital status and educational level among adventure tourists who had visited Malaysia [63]. Similarly, Rojo-Ramos et al found significant differences in the level of education and professional status when assessing gender in adventure tourists [62]. It is worth mentioning the scarce bibliography with a segmentation of the different tourism sectors, in this case adventure tourism, in which the dependent variable is gender.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, in Norwegian domestic tourism in the nature activities sector, the predominant demographic profile included both genders, an age between 35 and 44 years old, married, with a high school education and no children. In the Spanish context and more specifically in Extremadura, adventure tourists tend to be Spanish, single, university educated, with permanent employment contracts, with children at home and with a median age of 40 [62]. As for gender, previous research had already pointed out possible distribution differences in terms of professional status, marital status and educational level among adventure tourists who had visited Malaysia [63].…”
Section: Discussionmentioning
confidence: 99%